2023
DOI: 10.1007/s00381-023-05982-5
|View full text |Cite
|
Sign up to set email alerts
|

ICP, PRx, CPP, and ∆CPPopt in pediatric traumatic brain injury: the combined effect of insult intensity and duration on outcome

Abstract: Purpose The aim was to investigate the combined effect of insult intensity and duration, regarding intracranial pressure (ICP), pressure reactivity index (PRx), cerebral perfusion pressure (CPP), and optimal CPP (CPPopt), on clinical outcome in pediatric traumatic brain injury (TBI). Method This observational study included 61 pediatric patients with severe TBI, treated at the Uppsala University Hospital, between 2007 and 2018, with at least 12 h of ICP da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…131 Additionally, ICP is not a dichotomous parameter, and both the magnitude and duration of ICP elevations are associated with worse outcomes (pressure-time burden). 124,125,132,133 Güiza and colleagues demonstrated that children suffer injury at lower ICP burdens than adults and that cerebral autoregulation (CA) status is an important determinant of ICP tolerance. 124 While awaiting further prospective studies that could inform modifications of current guidelines, clinicians should consider age, and possibly autoregulation status, when establishing ICP/CPP goals.…”
Section: Invasive Monitoring Of Intracranial Pressure and Cerebral Pe...mentioning
confidence: 99%
See 3 more Smart Citations
“…131 Additionally, ICP is not a dichotomous parameter, and both the magnitude and duration of ICP elevations are associated with worse outcomes (pressure-time burden). 124,125,132,133 Güiza and colleagues demonstrated that children suffer injury at lower ICP burdens than adults and that cerebral autoregulation (CA) status is an important determinant of ICP tolerance. 124 While awaiting further prospective studies that could inform modifications of current guidelines, clinicians should consider age, and possibly autoregulation status, when establishing ICP/CPP goals.…”
Section: Invasive Monitoring Of Intracranial Pressure and Cerebral Pe...mentioning
confidence: 99%
“…[136][137][138] It increases vulnerability to secondary insults and is independently associated with worse outcomes. 132,[139][140][141][142][143][144][145][146][147] The most studied CA assessment method is the pressure reactivity index (PRx), which uses spontaneous variations in mean arterial pressure (MAP) to calculate a moving correlation coefficient (À1 to þ1) between ICP and MAP. 144 With intact CA, PRx should be zero or negative.…”
Section: Cerebral Autoregulation and Pressure-reactivity Indexmentioning
confidence: 99%
See 2 more Smart Citations